2022
DOI: 10.3389/fnut.2022.968868
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin D status and the anti-seizure treatment in Chinese children with epilepsy

Abstract: ObjectiveTo compare the serum 25-OH-VitD levels, the major marker of vitamin D (VitD) status, between healthy children and children with epilepsy before initiation of and during anti-seizure medications (ASMs) treatment and to evaluate the potential influence factors on 25-OH-VitD levels. Another major aim was to assess the potential role of VitD supplementation.MethodsFor comparison, we finally enrolled and collected data from 6,338 healthy children presenting to Health Care Department and 648 children visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…However, although some studies of patients with epilepsy have identi ied a therapeutic bene it of vitamin B6 supplementation in terms of improved clinical outcomes, this is not the case for every patient [212][213][214][215][216][217][218]. Multiple studies have identi ied vitamin D de iciencies among pediatric and adult patients with epilepsy [219][220][221][222]. In one clinical trial involving 23 patients with epilepsy administered 4,000 IU/day of vitamin D3 was for 4 weeks followed by 16,000 IU/day for 4 weeks to one group and a placebo followed by 8,000 IU/day of vitamin D3 to another.…”
Section: Epilepsy and Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although some studies of patients with epilepsy have identi ied a therapeutic bene it of vitamin B6 supplementation in terms of improved clinical outcomes, this is not the case for every patient [212][213][214][215][216][217][218]. Multiple studies have identi ied vitamin D de iciencies among pediatric and adult patients with epilepsy [219][220][221][222]. In one clinical trial involving 23 patients with epilepsy administered 4,000 IU/day of vitamin D3 was for 4 weeks followed by 16,000 IU/day for 4 weeks to one group and a placebo followed by 8,000 IU/day of vitamin D3 to another.…”
Section: Epilepsy and Nutrientsmentioning
confidence: 99%
“…Studies using animal models of epilepsy have found vitamin D to have anticonvulsive effects and knocking out the vitamin D receptor signi icantly increases seizure frequency in mouse models of epilepsy [224]. Another study of 648 children with epilepsy found improved seizure control with vitamin D supplementation [222].…”
Section: Epilepsy and Nutrientsmentioning
confidence: 99%
“…27 Most observational studies have shown that 25 (OH) D level is decreased by taking antiepileptic drugs, and 25 (OH) D supplementation can reduce seizure frequency . 6,28,29 However, some studies have shown that 25 (OH) D supplementation does not reduce seizure frequency in patients with drug-resistant epilepsy. 8 As can be seen from the above, there is a contradiction in whether 25 (OH) D prevents epilepsy or controls seizure frequency in observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…43 In Chinese pediatric patients, a comparable outcome of seizure control was observed following the administration of Vitamin D supplementation, with the proportion of individuals achieving seizure-free rising from an initial 49% to a final 76%. 44 According to its molecular structure, bioactivation in the nervous system, and mechanism of action, Vitamin D3 can be classified as a neurosteroid hormone rather than a vitamin. 45 The presence of the Vitamin D activating 1-α-hydroxylase enzyme and Vitamin D receptor (VDR) has been observed in various brain structures, including neuronal and glial cells.…”
Section: Bone Healthmentioning
confidence: 99%